Weaving Imagination: Integrating Artificial Intelligence Into Art Learning to Enhance Student Creativity - Tri Wahyu Martiningsih (Yayasan Adra Karima Hubbi, 2025)
Background. The integration of artificial intelligence (AI) into education presents transformative opportunities, particularly in the domain of art learning, where creativity is both the process and the product. This study is grounded in the increasing need to reimagine art education by leveraging digital technologies to stimulate and scaffold student imagination and creative expression. Purpose. The research aims to explore how AI-based tools can be effectively utilized within the art learning environment to enhance students’ creative thinking and artistic innovation. Method. Employing a qualitative case study approach, data were collected through classroom observations, student artwork analysis, and in-depth interviews with teachers and students from a secondary school implementing AI-assisted art activities. Results. The findings reveal that the use of AI—especially generative models—positively influences students' ideation processes, broadens their aesthetic perspectives, and fosters a sense of co-creation between human and machine. Furthermore, the study highlights the pedagogical strategies that optimize AI integration, including guided experimentation, reflective discussion, and iterative design. Conclusion. The research concludes that AI, when meaningfully embedded into art instruction, acts not as a replacement for human creativity but as a catalyst that amplifies students’ imaginative capacities.